ISSUES OF STADIYING THE LITERARY AND SCIENTIFIC HERITAGE OF ALISHER NAVOI (Ustozlar uchun, 2025)
A huge exponent of Uzbek literature and culture,  a poet and a thinker who contributed immensely to the development of Turkic poetry. He introduced  his work “Khamsa” to the world heritage of Uzbek literature. In Navoi’s   works, universal human values such as humanity, justice ,       enlightenment and love are depicted with high artistic skill. He lift a huge legacy not only in literature, but also in public  administration, linguistics, philosophy and social issues. In the work  “Muhokamat-ul lugatayn”, the wealth and possibilities  of the turky language were demonstrated  and made a significant contribution to its development. Navoi creativity serves as not only an invaluable  source of artistic works for Uzbek culture,  but also a foundation for spiritual upliftment. His works continue to anrich the spiritual heritage of the modern Uzbek people.